PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA PEGAWAI PADA KANTOR KECAMATAN MAIWA KABUPATEN ENREKANG - Wirna Wirna; Sapri Sapri; Andi Uceng; Jamaluddin Ahmad; Sahar Sahar (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
This research was conducted to find out how much influence human resource management has on employee performance at the Maiwa District Office, Enrekang Regency which was carried out through distributing questionnaires to 22 Maiwa District Office employees and 30 Maiwa District residents where based on the results of data processing carried out the results of the R2 determination test were obtained. where the R value is 0.414, which means that human resource management has a sufficient influence on improving the performance of the Maiwa District Office, Enrekang Regency employees by 41% and based on the results of hypothesis testing using F-test analysis on the basis of decision making the value Fcount > Ftable and the results obtained are 10.333 > 4.03 with a significant level of 0.005 and the result is 0.002 which means that the influence between human resource management on improving the performance of the Maiwa District Office, Enrekang Regency is acceptable and has a positive and significant effect. significant coup.